Understanding School Safety and the Use of School Resource Officers in Understudied Settings: Survey Data, Southern United States, 2017 - Curran, F. Chris ([Verlag nicht ermittelbar], 2020)
The Understanding School Safety and the Use of School Resource Officers in Understudied Settings project investigated school resource officers (SROs) within settings that have received almost no attention in the empirical literature: elementary schools and affluent, high performing school districts. This project was guided by four research questions: 1) Why and through what process were SROs implemented? 2) What roles and activities do SROs engage in within schools? 3) What impacts do SROs have on schools and students? 4) How do the roles and impacts of SROs differ across school contexts? Survey data come from the districts' SROs, and a sample of teachers, school leaders, students, and parents. Survey data was collected between spring of 2017 and fall of 2017.